The PERK Branch of the Unfolded Protein Response Safeguards Protein Homeostasis and Mesendoderm Specification of Human Pluripotent Stem Cells - Liu, Fang; Liu, Zhun; Cheng, Weisheng; Zhao, Qingquan; Zhang, Xinyu; Zhang, He; Yu, Miao; Xu, He; Gao, Yichen; Jiang, Qianrui; Shi, Guojun; Wang, Likun; et al. (Advanced science, 2023)
Cardiac development involves large‐scale rearrangements of the proteome. How the developing cardiac cells maintain the integrity of the proteome during the rapid lineage transition remains unclear. Here it is shown that proteotoxic stress visualized by the misfolded and/or aggregated proteins appears during early cardiac differentiation of human pluripotent stem cells and is resolved by activation of the PERK branch of unfolded protein response (UPR). PERK depletion increases misfolded and/or aggregated protein accumulation, leading to pluripotency exit defect and impaired mesendoderm specification of human pluripotent stem cells. Mechanistically, it is found that PERK safeguards mesendoderm specification through its conserved downstream effector ATF4, which subsequently activates a novel transcriptional target WARS1, to cope with the differentiation‐induced proteotoxic stress. The results indicate that protein quality control represents a previously unrecognized core component of the cardiogenic regulatory network. Broadly, these findings provide a framework for understanding how UPR is integrated into the developmental program by activating the PERK‐ATF4‐WARS1 axis. The development of the heart involves extensive rearrangements of the proteome. However, it remains unclear how developing cardiac cells uphold proteome integrity amidst swift lineage transition. This study highlights the crucial role played by the PERK branch of unfolded protein response to resolve differentiation‐induced proteotoxic stress, thereby safeguarding initial cardiac specification in human pluripotent stem cells.